Arts therapies and new challenges in psychiatry - Dannecker, Karin (Abingdon, Oxon ; New York, NY : Routledge, 2018)
"Despite their increasing popularity and reported effectiveness, there is a dearth of evidence-based research on the practices that fall under the umbrella of "the arts therapies". The successful treatment of a variety of psychiatric illnesses through the application of the arts therapies has long been recognized in many countries around the world, including psychosis, schizophrenia, depression and borderline symptoms.? Providing valuable data on the effectiveness of the arts therapies, Arts Therapies and New Challenges in Psychiatry fills an important gap in the literature on psychiatric illnesses. Contributors to this impressive volume have carried out research in psychiatry and mental health with patients diagnosed with a variety of illnesses. The international focus of the book shows the global, cross-cultural relevance of the arts therapies, whilst quantitative and qualitative evidence is used to demonstrate the need for art-, music-, drama- and dance therapy in a wide variety of contexts. This book shows that research in these fields can be carried out convincingly using a broad range of approaches, including each field's own professional matrix. Providing a much-needed assessment of the arts therapies, this book will appeal to art therapists, music therapists, dance therapists and drama therapists, as well as psychiatrists, psychologists, psychoanalysts and educators of arts therapy training."--Provided by publisher.
Music therapy : differentiation of emotions in schizophrenia / Susanne Bauer -- From the "inside feeling" to narration : symbolization and aesthetic emotion in music therapy / Christine Falquet-Clin and Edith Lecourt -- Dramatherapy work in the treatment of schizophrenic psychoses / Johannes Junker -- Therapeutic effects of brief group interactive art therapy with war veterans / Alexander Kopytin and Alexey Lebedev -- A neglected area in schizophrenia treatment and research : the efficacy of art therapy. Results of a randomised controlled trial and qualitative study / Christiane Montag and Karin Dannecker -- Changes in well-being of schizophrenic patients after movement therapy : results of a multicenter RCT study / Valerie Pohlman, Sabine Koch and Thomas Fuchs -- Adapting Winnicott's squiggle technique in group art therapy to a psychotic population undergoing a psychosocial rehabilitation programme / Alice Reid -- The borrowed image in art therapy with psychiatric patients : the internalization process / Elizabeth Stone-Matho -- Longing for belonging / Zuzana Vasicak Oecenaesova and Iveta Koblic Zedkova -- Assessing negative symptoms of schizophrenia by the use of Aristotle's poetics during a dramatherapy process / Lambros Yotis.
Keywords: Art therapy